Persistent abdominal pain over uterine scar during labor as a predictor of delivery complications. Issue 3 (31st August 2013) - Cohen, Aviad; Cohen, Yoni; Laskov, Ido; Maslovitz, Sharon; Lessing, Joseph B.; Many, Ariel
Abstract: Objective: To evaluate the significance of persistent lower abdominal pain in women with previous cesarean delivery. Methods: Various maternal outcomes were compared between women who underwent repeated cesareans owing to persistent lower abdominal pain (study group) and women who underwent repeated cesareans without persistent abdominal pain (control group). Results: The incidence of uterine rupture was significantly higher in the study group than in the control group (8/81 [9.9%] vs 0/119 [0.0%]; P < 0.001). While all women with persistent lower abdominal pain and uterine rupture had an additional sign or symptom, only 6/73 (8.2%) women with persistent abdominal pain without uterine rupture had any additional symptoms (P < 0.001). There was no difference in incidence of uterine scar dehiscence between the groups. However, the hospitalization period was significantly longer in the study group (4 vs 3.7 days; P < 0.05). Trial of labor was a contributing factor to uterine rupture. Conclusion: Isolated persistent lower abdominal pain in women with previous cesarean is a poor indicator of uterine rupture. However, the positive predictive value for uterine rupture is 57% when an additional sign or symptom is present. Dehiscence of the uterine scar is relatively common and it is not associated with persistent abdominal pain.